Proceedings Design, Automation and Test in Europe Conference and Exhibition
DOI: 10.1109/date.2004.1268820
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid architectural dynamic thermal management

Abstract: new, "hybrid," low-overhead implementation based on combining fetch gating and dynamic voltage scaling (DVS). When thermal stress is low, fetch gating is superior because it exploits instruction-level parallelism (ILP). Once thermal stress becomes severe enough that fetch gating degrades ILP, DVS is engaged instead to take advantage of its greater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…In [6], they introduce temperature-tracking based frequency scaling, localized toggling and computation migration to spare hardware units. In [7], they propose a hybrid DTM technique that combines fetch gating and DVS. In [8], they propose a formal feedback control theory and use DTM as a test vehicle.…”
Section: Prior Workmentioning
confidence: 99%
“…In [6], they introduce temperature-tracking based frequency scaling, localized toggling and computation migration to spare hardware units. In [7], they propose a hybrid DTM technique that combines fetch gating and DVS. In [8], they propose a formal feedback control theory and use DTM as a test vehicle.…”
Section: Prior Workmentioning
confidence: 99%
“…Instead, packages are designed for worst typical behavior and rely on Dynamic Thermal Management (DTM) techniques to control the temperature. Many hardware and softwarebased DTM techniques have been proposed recently [3,6,7,12,13,15]. Most of them, with the exception of [15], are reactive in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Skadron, et al suggested several schemes for the thermal management including temperature-tracking [11], hybrid scheme [9], and feedback control [10,8]. In [11], temperature-tracking scheme manages temperature based on frequency scaling, localized toggling, and computation migration.…”
Section: Related Workmentioning
confidence: 99%
“…In [11], temperature-tracking scheme manages temperature based on frequency scaling, localized toggling, and computation migration. In [9], they proposed a hybrid scheme between fetch gating and DVFS. Also, a feedback control configures the temperature based on feedback information [10,8].…”
Section: Related Workmentioning
confidence: 99%